Arabic and Dialectal Diversity: Is the Maltese Tongue an Evolved Arabic Dialect? (Linguist, 2025)
The study of dialects in modern linguistic research holds paramount importance in uncovering the nature of the differences that arise between a language and its dialects, as well as the issues they entail. Among these is the contribution to analyzing the linguistic evolution accompanying the formation of various linguistic levels within a language. In this study, we seek to explore questions concerning the true nature of the Maltese language, whose vocabulary and expressions suggest that it initially emerged as a dialect branching from tunisian Arabic and sicilien arabic. Over time, however, it evolved into an independent language with its own phonetic, morphological, syntactic, and semantic rules, thereby forming the linguistic identity of a nation within the specific geographical space of the Maltese islands. We have based this hypothesis on concrete examples and evidence drawn from the Maltese lexicon, comparing it with the lexicon of Arabic, Tunisian arabic and Sicilian Arabic.
Keywords: Language; tongue; Maltese language; Tunisian arabic; Sicilien arabic; phonetics of Maltese language; Language life